(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Describe the clinical and paraclinical characteristics of children treated with percutaneous atrial septal defect closure at Nghe An Obstetrics and Pediatrics Hospital in the period of 2018 – 2023. Research Methods: Cross-sectional descriptive study with analysis. Results: Study of 33 patients diagnosed with atrial septal defect with indication for percutaneous parachute closure treated at the Cardiology Department of Nghe An Obstetrics and Pediatrics Hospital. Information was collected by examination and pre-designed medical records. Results: The female/male ratio was 1.36/1, the average age at the time of percutaneous parachute closure intervention was 5.39 ± 3.02 years old. Common clinical manifestations in children with atrial septal defect were heart failure (42.4%) and recurrent pneumonia (39.4%), clinical systolic murmur (100%) and split S2 (27.3%); Paraclinical: Chest X-ray shows increased pulmonary circulation (87.9%), enlarged heart (42.4%); ECG shows increased right ventricular load (81.8%), right axis (66.7%), incomplete right bundle branch block (45.5%); Doppler echocardiography shows that 78.8% of patients have large atrial septal defect, 21.2% have moderate atrial septal defect, right ventricular dilatation (60.6%) and increased pulmonary artery pressure (45.5%). Conclusion: Clinical examination, X-ray, ECG, Doppler echocardiography have diagnostic value to determine atrial septal defect as well as assess hemodynamic consequences and clearly describe the morphology, location and size of the defect. From there, having the right indications to bring optimal treatment results is extremely important for physicians.